Performance Analysis of Aes and 3des for Implementing Multi Level Authentication in Cloud Through Rest Api - J. Balachandran, M.; Sujatha, P. (International Journal of Engineering and Technology, 2018)
Last couple of decades, internet usage has been changed each and every technology domain. This has lead to implementation and accommodation of cloud computing. As the Cloud has the nature of sharing the data, it led to various types of security attacks. Hence security mechanisms which has various features/types are needed and hence security breaches can be prevented. Authentication is one of the vital techniques playing a major role in security part. Cloud Computing verifies the identification of a user during the process of accessing the services from cloud servers. Different authentication techniques are used to verify the user’s identity before granting the access to them.  This paper  analyze the performance of AES and  3DES algorithms and find out the best suit for implementing multi level authentication in cloud. Based on execution time, request and response time against the concurrent user load and file size, AES is faster, more secure and safer than 3DES.